Student attitudes toward the use of Facebook in higher education: Implications for the learning experience - Marković Marija; Stanisavljević-Petrović Zorica (CM. Communication and Media)
In light of the growing importance of digital technologies and the rise of social networks, understanding the role of Facebook in higher education has become increasingly pertinent. This study aims to investigate university students' attitudes toward the use of Facebook as a tool for both direct and indirect academic engagement, with particular focus on its role in supporting learning, communication, and collaboration. A descriptive method was used, with data collected from 314 undergraduate students at the Faculty of Philosophy, University of Niš. The results indicate that students highly value Facebook for information exchange and sharing academic materials, but are generally cautious about its direct application in learning processes. The study also examines the influence of independent variables (such as study program, academic performance, duration of Facebook use, and frequency of access) on student attitudes. The pedagogical implications of these findings may contribute to enhancing the use of Facebook and other digital platforms in higher education, both for direct academic purposes and broader educational experiences.